Influence of age, sex, and presence of cleft lip and palate on the quantity and quality of saliva-derived DNA - Lina M. Escobar; Zita Bendahan; Deisy Abril; David Díaz-Baez; Adolfo Paternina; Farith González-Martinez; Ma Clara González-Carrera (Journal of Oral Biology and Craniofacial Research)
The quantity and quality of DNA are crucial factors in determining polymorphisms in samples from individuals with and without pathologies such as cleft lip and palate (CL/P). Saliva is increasingly being evaluated as a collection method. This study aimed to compare saliva DNA concentrations from individuals of different ages with and without CL/P.Saliva samples were collected, DNA was extracted and the quantification was performed by spectrophotometry. Kruskal-Wallis test was used to compare frequencies between groups, and Spearman's rho for correlations.We obtained saliva DNA from 314 individuals: 107 with CL/P (mean age: 12.7 ± 6.5 years), 103 parents of children with CL/P (mean age: 41.1 ± 9.3 years), 52 individuals without CL/P under 18 years old (controls), and 52 individuals without CL/P over 18 years old (controls). The sample comprised 32.2 % females and 67.8 % males.Statistically significant differences in DNA concentrations were found between individuals under and over 18 years old (12.38 and 21.3 ng/μl, respectively, p = 0.0001), but no differences were observed between males and females. Individuals with CL/P had lower DNA concentrations (12.45 ng/μl) compared to their parents and controls (21.95 and 21.15 ng/μl, respectively). Our results showed a direct correlation between age and DNA concentration in individuals with CL/P under 18 years old (R = 0.328).